Linear Neterov’s boundary problems for differential systems with pulse action - Samoilenko , A. M.; Boichuk , A. A. (Ukrains’kyi Matematychnyi Zhurnal, 1992)
A solvability criterion of linear nonhomogeneous boundary value problems is obtained for systems of ordinary differential equations with impulse action in the general case when the number of boundary conditions does not coincide with the order of the differential system (Noetherian problems). The generalized Green operator of such boundary value problems is constructed. Its connection with the generalized inverse operator of the operator of the original boundary value problem is shown.